Enhancing quality management through intra- and inter-plant integration in manufacturing networks. (2nd April 2020) - Shou, Yongyi; Li, Lingjia; Kang, Mingu; Park, Youngwon
Abstract : This study investigates the relationships among quality management (QM), integration and business performance in the context of manufacturing networks. Specifically, two kinds of integration in manufacturing networks are examined: intra-plant integration (integration across functions within a plant) and inter-plant integration (integration across plants within a manufacturing network). An international survey of 493 manufacturing plants was used to test the hypothesised relationships. Results show that both intra-plant integration and inter-plant integration enhance QM practices and business performance. Moreover, intra-plant integration is a prerequisite for inter-plant integration while inter-plant integration has a more significant effect on QM than intra-pant integration does.